Caring for a patient with rabies: implications of the Milwaukee protocol for infection control and public health measures. Issue 4 (August 2017) - Lampejo, T.; Bruce, M.; Teall, A.; Dall'Antonia, M.; Crawley-Boevey, E.; Grant, P.; Polhill, S.; Pillay, D.; Brown, D.; Brown, M.; Nastouli, E.
Summary: This article discusses the infection control and public health measures taken whilst managing a case of laboratory-confirmed rabies, and the challenges faced in implementing these measures. Case management requires intensive multi-disciplinary co-ordination. The Milwaukee protocol, which to date has five reported human rabies survivors associated with its use, has been suggested as a potential management pathway for human rabies. Consensus among hospital and public health clinicians would aid future deployment of this approach in selected cases.